2005 First International Conference on Semantics, Knowledge and Grid 2005
DOI: 10.1109/skg.2005.116
|View full text |Cite
|
Sign up to set email alerts
|

SPN Model for Web Prefetching and Caching

Abstract: The World Wide Web has become the primary means for information dissemination. Due to the limited resources of the network bandwidth, users always suffer from long time waiting. Web prefetching and Web caching are the primary approaches to reducing the user perceived access latency and improving the quality of service. In this paper, a SPN (Stochastic Petri Nets) model of Web prefetching and caching system is constructed, and based on which, the performance analysis of the integrated Web prefetching and cachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…These techniques result in effective document prefetching with efficient buffer size management, but, buffer management can cause additional overhead. Shi et al (2005) propose a new model for integration of web caching and web prefetching called the stochastic petri nets (SPN) model in a server-side proxy. Caching and prefetching are classified into two different categories: passive caching, where only caching takes place, i.e., the accessed documents are stored in the cache for future reference, and local prefetching, where objects are prefetched and cached based only upon the local information available in the client.…”
Section: Related Workmentioning
confidence: 99%
“…These techniques result in effective document prefetching with efficient buffer size management, but, buffer management can cause additional overhead. Shi et al (2005) propose a new model for integration of web caching and web prefetching called the stochastic petri nets (SPN) model in a server-side proxy. Caching and prefetching are classified into two different categories: passive caching, where only caching takes place, i.e., the accessed documents are stored in the cache for future reference, and local prefetching, where objects are prefetched and cached based only upon the local information available in the client.…”
Section: Related Workmentioning
confidence: 99%
“…Meanwhile, researchers have found that access to cloud data follows the Zipf-like law [24] and have used this law to design cache and prefetch systems. Shi et al proposed a web prefetching and cache model based on Petri nets, combining prefetching with caching to improve the service quality of distributed storage systems [25].…”
Section: Introductionmentioning
confidence: 99%